The social networks of Hong Kong Chinese family caregivers of Alzheimer's disease: correlates with positive gains and burden - Cheng, Sheung-Tak; Lam, Linda C W; Kwok, Timothy; Ng, Natalie S S; Fung, Ada W T (The Gerontologist, 2013)
To examine the social networks of family caregivers of persons with Alzheimer's disease and the degree to which network characteristics were associated with satisfaction with social support, burden, and positive gains. A total of 142 Chinese caregivers responded to measures of structural support, positive exchanges, and negative exchanges using the social convoy questionnaire, as well as to measures of social support satisfaction, burden, role overload, positive gains, self-rated health, and behavioral and psychological symptoms of dementia (BPSD) of the care recipient. Data were analyzed using multiple regression. The caregivers had small networks (mean = 4.4 persons). They reported few negative exchanges with network members and higher emotional than instrumental support, while being rather satisfied with the social support obtained. Surprisingly, both spouse/sibling and adult child caregivers excluded many close kin, in particular ~40% of their children, from their networks. A larger network was associated with higher social support satisfaction and positive gains, and lower role overload. Controlling for network size and social support satisfaction, positive exchanges were associated with higher positive gains, whereas negative exchanges were associated with higher burden and overload. Caregivers who experienced more BPSD and poorer self-rated health also reported lower support satisfaction and positive gains, as well as higher burden and overload. Under the influence of collectivism, individuals may shoulder the responsibilities of caregiving for the collective well-being of the family and end up being isolated and disappointed when expectations of family support were not forthcoming, to the extent that even ties with close kin may be severed.